Microstructure and corrosion resistance of Fe-Al intermetallic coating on 45 steel synthesized by double glow plasma surface alloying technology - 朱晓林 姚正军 顾雪冬 丛伟 张平则 (Transactions of Nonferrous Metals Society of China, 2009)
A binary Fe-Al alloyed layer was synthesized on 45 steel by means of double glow plasma surface alloying technique. The corrosion-resisting layer prepared is composed of a sedimentary layer and a diffusion layer, with a total thickness of about 180 μm. The aluminum content of the alloyed layer shows gradual change from surface to the inside of substrate. The ideal profile is beneficial to the metallurgical bonding of the surface alloying layer with substrate materials. The microstructure of both layers consists of the Fe-AI intermetallic compound, which is FeA1 with B2 structure in the sedimentary layer and Fe3A1 with incompletely ordered DO3 structure in the diffusion layer. The protective film exhibits high micro-hardness. In comparison with the substrate of 45 steel, the corrosion resistance of the aluminized sample is much higher in 2.0% Na2S and 0.05 mol/L Na2SO4 ＋ 0.5 mol/L NaCl mixed solutions.